Praktik Manajemen Laba dengan Mempertimbangkan Ukuran Perusahaan: Studi pada Sub Klasifikasi Industri Dasar dan Kimia di Bursa Efek Indonesia - Subikhi, Alif Akbar; Sari, Shinta Permata; Fatahuddin, Amir (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2020)
Earnings management is the effort of a manager to manipulate financial statements in order to get the benefits in accordance with their wishes. This behavior is considered as deviant action due to the fact that managers provide biased information that can mislead financial statements users. This study aims to analyze the effect of firm size measured by total assets and total sales on earnings management practices. The sample use in this study is manufacturing companies in the basic and chemical industrial classification which are listed on the Indonesia Stock Exchange in the 2017-2018 period and collected using purposive sampling methods. The data obtain 30 companies and summarize from company’s annual report. This study uses multiple linear regression to analyze sample’s data. The results show that the firm size measured by total assets and total sales effect earnings management practices.